The Importance of Increasing Tolerance for All Indonesia Citizens as an Effort to Practice the First Precept in Pancasila in the Life of the Nation and State - Anantasya, Yohana Agnes Dewi; Sanjaya, Dewa Bagus; Yanti , Putu Dea Anggita; Dakhi, Risti Tiarna Putri; Evayani, Kadek Dwi; Maulida , Rosalina; Sipayung, Marisa Yolan Br; Ifyani, Naila (Jurnal Pendidikan Kewarganegaraan Undiksha, 2025)
Religious and belief diversity is an inseparable reality of the Indonesian nation. This study aims to gain a deeper understanding of the concept of tolerance, explore the meaning of citizenship, enhance knowledge about the importance of the first principle of Pancasila, identify actions that hinder the sense of tolerance among Indonesian citizens, and suggest strategies or methods to improve tolerance among all Indonesian citizens in the context of national and state life. This research uses document study as its method, by collecting materials from journals, articles, books, and references from internet-based documents. The results of the study show that there are still many irresponsible acts of intolerance by members of Indonesian society toward people of different religions, which has negative impacts on national and state life. This issue can be addressed by continuously encouraging people to develop a sense of empathy and mutual care for one another, despite religious differences. This approach is one of the efforts to increase the sense of tolerance among all Indonesian citizens in national life, so that in the future, Indonesia can become a nation that lives in shared prosperity, even with its diverse backgrounds.